1982
DOI: 10.1002/1097-0142(19820101)49:1<35::aid-cncr2820490108>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced tumor regression as a prognostic factor in patients with invasive cervical cancer

Abstract: Radiation-induced tumor regression was evaluated as a prognostic factor in 200 patients with invasive cervical cancer treated at the University of Kentucky Center during the years 1973-1977. Radiation responses were classified as complete (Type A), intermediate (Type B), or incomplete (Type C) based upon pelvic examination findings one month following completion of therapy. Patients with Type A response to radiation had a recurrence rate of 5%, as compared with 27% in patients with a Type B response and 85% in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
1

Year Published

1984
1984
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(12 citation statements)
references
References 13 publications
3
8
1
Order By: Relevance
“…In the present study, the status of early volumetric changes assessed by MRI correlated with progression-free and overall survival. These results are consistent with earlier studies showing that early regression during or immediately after RT is a predictor of outcome of cervical cancer [4][5][6][7] .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, the status of early volumetric changes assessed by MRI correlated with progression-free and overall survival. These results are consistent with earlier studies showing that early regression during or immediately after RT is a predictor of outcome of cervical cancer [4][5][6][7] .…”
Section: Discussionsupporting
confidence: 93%
“…Marcial et al [4] and Grossman et al [5] reported a correlation between early tumor regression and the probability of permanent control. Hardt et al [6] and Jacobs et al [7] concluded that patients with no residual tumor 1 month after treatment had a marked survival advantage. These studies suggest that screening for patients with poor prognostic signs is important, in order that adjuvant treatment be started as early as possible.…”
mentioning
confidence: 99%
“…This observation has been confirmed, suggesting that there are differences in the radiosensitivity of cervical carcinomas [52,58,88].…”
Section: Other Possible Prognostic Factorsmentioning
confidence: 59%
“…Tumor regression was chosen as a short-term endpoint because it has been shown to correlate with local control and outcome (18,19). Tumors with a higher level of perfusion and permeability have a better prognosis.…”
Section: Discussionmentioning
confidence: 99%